Chusovoy Urban District in the Territorial System of the Perm Krai: Historical and Geographical Analysis - A. S. Luchnikov; I. S. Rudakova (Историко-географический журнал)
Chusovoy urban district of the Perm Krai is one of the central municipalities in the east of the region, within the so-called Gornozavodsky Prikamye. At present, the city and the territories adjacent to it are included in the official list of the Ministry of Economic Development of the Russian Federation as a single-industry settlement with a difficult socio-economic situation. One of the reasons for this situation was the reduction in the activity of the city-forming functions, associated with the lack of a diversified urban economy and the creation of a negative image of the city. Based on the historicalgenetic approach and the identification of the main factors (driving reasons), the article characterizes five stages of the socio-economic development of the Chusovoy lands and the city of Chusovoy as a part of the territorial system of the Perm Krai. The most important events and decisions that have become a turning point in the history of the development of the territories between the Chusovaya and Us’va rivers are indicated. It is determined that consideration of the functions characteristic of the city in the past will help to substantiate the promising directions of its development in the future. When considering the current stage of development of the district, special attention is paid to the implementation of the concept of a new industrial policy, which implies the modernization of traditional functions for the urban economy, the emergence of new types of activities (as part of stimulating small and medium businesses) and post-industrialization, i.e. active use of the historical and industrial heritage of Chusovoy for the development of the tourist and recreational sphere and other modern service activities.